Isobutanol Production by Autotrophic Acetogenic Bacteria - Weitz, Sandra; Hermann, Maria; Linder, Sonja; Bengelsdorf, Frank R.; Takors, Ralf; Dürre, Peter (Frontiers in Bioengineering and Biotechnology, 2021)
Two different isobutanol synthesis pathways were cloned into and expressed in the two model acetogenic bacteria Acetobacterium woodii and Clostridium ljungdahlii. A. woodii is specialized on using CO2 + H2 gas mixtures for growth and depends on sodium ions for ATP generation by a respective ATPase and Rnf system. On the other hand, C. ljungdahlii grows well on syngas (CO + H2 + CO2 mixture) and depends on protons for energy conservation. The first pathway consisted of ketoisovalerate ferredoxin oxidoreductase (Kor) from Clostridium thermocellum and bifunctional aldehyde/alcohol dehydrogenase (AdhE2) from C. acetobutylicum. Three different kor gene clusters are annotated in C. thermocellum and were all tested. Only in recombinant A. woodii strains, traces of isobutanol could be detected. Additional feeding of ketoisovalerate increased isobutanol production to 2.9 mM under heterotrophic conditions using kor3 and to 1.8 mM under autotrophic conditions using kor2. In C. ljungdahlii, isobutanol could only be detected upon additional ketoisovalerate feeding under autotrophic conditions. kor3 proved to be the best suited gene cluster. The second pathway consisted of ketoisovalerate decarboxylase from Lactococcus lactis and alcohol dehydrogenase from Corynebacterium glutamicum. For increasing the carbon flux to ketoisovalerate, genes encoding ketol-acid reductoisomerase, dihydroxy-acid dehydratase, and acetolactate synthase from C. ljungdahlii were subcloned downstream of adhA. Under heterotrophic conditions, A. woodii produced 0.2 mM isobutanol and 0.4 mM upon additional ketoisovalerate feeding. Under autotrophic conditions, no isobutanol formation could be detected. Only upon additional ketoisovalerate feeding, recombinant A. woodii produced 1.5 mM isobutanol. With C. ljungdahlii, no isobutanol was formed under heterotrophic conditions and only 0.1 mM under autotrophic conditions. Additional feeding of ketoisovalerate increased these values to 1.5 mM and 0.6 mM, respectively. A further increase to 2.4 mM and 1 mM, respectively, could be achieved upon inactivation of the ilvE gene in the recombinant C. ljungdahlii strain. Engineering the coenzyme specificity of IlvC of C. ljungdahlii from NADPH to NADH did not result in improved isobutanol production.